1st separate rifle corps at the border of the Smykov-Grigoropolis - A. V. Kartashev (Гуманитарные и юридические исследования)
The article is devoted to the little-known fact of the fighting of Soviet troops in the west of the Stavropol Territory in the period from 3 to 5 August 1942. This episode is not considered in detail in the literature about the Battle for the Caucasus by A.A. Grechko, S.V. Yanush and other authors. An exception is the work devoted to assessing the personality of the commander of the 1st Separate Rifle Corps, Colonel M.M. Shapovalov, who defected to the enemy after leaving the city of Armavir. The village of Smykov and the village of Grigoropolisskaya were defended by formations and units of this corps, as well as other military formations of the Soviet troops retreating in this direction. Based on archival sources and memories, the course of military events is recreated, the purpose of these actions is shown: to provide cover for the troops of the 12th army retreating beyond the Kuban. A brief description of the Smykov line, Grigoropolis, is given, its advantages are shown. There is an explanation for the change in the plans of the command of the North Caucasus Front, when the previous task was canceled and this defensive line was assigned. This circumstance did not allow to prepare the defense efficiently, to ensure the inviolability of crossings across the Kuban River in the area of the village of Prochnookopskaya and the city of Armavir, as well as to defeat the enemy on the distant approaches to Maykop. The actions of the enemy are shown: the 13th Panzer Division of the Wehrmacht and the motorized SS division «Viking», which broke through the battle formations of corps rifle brigades. The complexity of the battles fought by the corps units with an inverted front, their intense and bloody nature, and the scale of losses of Soviet troops are revealed. The information is provided on the contribution of other formations and units to the defense of the right bank of the Kuban. The desire of the personnel to fulfill the assigned combat task is shown, the individual exploits of soldiers and commanders are described. The names of the officers of the command staff of the 1st Separate Rifle Corps, who, unlike the corps commander who betrayed the motherland, continued to fulfill their military duty to the end and passed the roads of war with honor.